Management Fisioterapi pada Kasus Osteoarthritis Lutut dengan Terapi Latihan Penguatan: Case Report - Sitti Qomariyah Diu; Sri Yunanto; Adnan Faris Naufal (Jurnal Medika Nusantara, 2025)
In individuals with osteoarthritis (OA), the knee is one of the main causes of functional limitations and pain in older adults. As a result, it will cause chronic knee joint pain, stiffness, decreased quality of life and physical disabilities such as difficulty walking, climbing stairs, and sitting and getting up from a chair. Impaired muscle function and decreased fitness can potentially be treated with exercise therapy. The purpose of this study was to determine the effectiveness of providing physiotherapy interventions combined with exercise therapy in cases of knee OA. The research method used a case report with single subject research conducted at Bagas Waras Klaten Hospital in April 2025. Subjects were given therapy interventions 3 times in 2 weeks with Infrared, TENS, Massage therapy and exercise therapy modalities, namely hip abductor strengthening exercise and quadriceps strengthening exercise. The results showed a decrease in pain evaluated using VAS, increased muscle strength using MMT, increased LGS using a goniometer, and increased functional ability using WOMAC. Suggestions for patients with knee OA include doing hip abductor strengthening exercise and quadriceps strengthening exercise therapy to help reduce pain and increase muscle strength so they can perform daily functional activities better.